Maternal Vibration: An Important Cue for Embryo Hatching in a Subsocial Shield Bug - Mukai, Hiromi (Public Library of Science, 2014)
Hatching care has been reported for many taxonomic groups, from invertebrates to vertebrates. The sophisticated care that occurs around hatching time is expected to have an adaptive function supporting the feeble young. However, details of the characteristics of the adaptive function of hatching care remain unclear. This study investigated the hatching care of the subsocial shield bug, Parastrachia japonensis (Heteroptera: Parastrachiidae) to verify its function. Results show that the P. japonensis mothers vibrated the egg mass intermittently while maintaining an egg-guarding posture. Then embryos started to emerge from their shells synchronously. Unlike such behaviors of closely related species, this vibrating behavior was faint, but lasted more than 6 h. To investigate the effect of this behavior on hatching synchrony and hatching success, we observed the hatching pattern and the hatching rate in control, mother-removed, and two artificial vibration groups. Control broods experienced continuous guarding from the mother. Intermittent artificial vibration broods were exposed to vibrations that matched the temporal pattern of maternal vibration produced by a motor. They showed synchronous hatching patterns and high hatching rates. However, for mother-removed broods, which were isolated from the mother, and when we provided continuous artificial vibration that did not match the temporal pattern of the maternal vibration, embryo hatching was not only asynchronous: some embryos failed to emerge from their shells. These results lead us to infer that hatching care in P. japonensis has two functions: hatching regulation and hatching assistance. Nevertheless, several points of observational and circumstantial evidence clearly contraindicate hatching assistance. A reduction in the hatching rate might result from dependence on maternal hatching care as a strong cue in P. japonensis. We conclude that the hatching care of P. japonensis regulates the hatching pattern and serves as an important cue to induce embryo hatching.